2021
DOI: 10.1161/circep.120.008540
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Related Changes in Left Atrial Structure in Atrial Fibrillation: Findings From the CABANA Imaging Substudy

Abstract: Background - The Catheter Ablation versus Antiarrhythmic Drug Therapy for Atrial Fibrillation (CABANA) trial was a randomized, prospective trial of left atrial catheter ablation versus drug therapy for treatment of atrial fibrillation (AF). As part of CABANA, a prospective imaging sub-study was conducted. The main objectives were to describe the patterns of changes in the dimensions of the left atrium (LA) and pulmonary veins (PVs), and the relationship between these changes with treatment assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…A prior study suggested a critical relationship between structural alterations of LA tissue and AF initiation addressing that PV dimensions seem to have a greater impact on AF recurrence than the pure size of the LA [23] and these findings are in line with our observations. Thus, preprocedural imaging and the estimation of the CSOA may help to identify patients who benefit most from single-shot device-guided PVI.…”
Section: Csoasupporting
confidence: 93%
“…A prior study suggested a critical relationship between structural alterations of LA tissue and AF initiation addressing that PV dimensions seem to have a greater impact on AF recurrence than the pure size of the LA [23] and these findings are in line with our observations. Thus, preprocedural imaging and the estimation of the CSOA may help to identify patients who benefit most from single-shot device-guided PVI.…”
Section: Csoasupporting
confidence: 93%
“…Intriguing GWAS studies have recently identified genetic loci for atrial dilatation [ 57 ]. A smaller LA volume index was associated with a lower risk for AF recurrence in the CABANA trial of ablation or pharmacotherapy [ 58 ]. Increasing data implicates right atrial enlargement in conferring a worse prognosis after ablation or cardioversion [ 59 , 60 ].…”
Section: Pathophysiology For Af At the Cellular Levelmentioning
confidence: 99%
“…In the CABANA imaging substudy, approximately 200 patients had pre-procedural and follow-up imaging (mean, 100 days) with either cardiac computed tomo graphy or magnetic resonance imaging (MRI) to quantify left atrial volumes and pulmonary vein (PV) diameter. 11 The left atrial volume index decreased 52.9% in the ablation group versus 40.0% in the AAD group. This finding is consistent with prior evidence that catheter ablation is associated with favorable remodeling that may result in long-term clinical benefits such as arrhythmia burden and stroke prevention.…”
Section: The East-af4net Trial and Early Treatment Of Atrial Fibrilla...mentioning
confidence: 90%